Amoxicillin Increased Functional Pathway Genes and Beta-Lactam Resistance Genes by Pathogens Bloomed in Intestinal Microbiota Using a Simulator of the Human Intestinal Microbial Ecosystem - Liu, Lei; Wang, Qing; Lin, Huai; Das, Ranjit; Wang, Siyi; Qi, Hongmei; Yang, Jing; Xue, Yingang; Mao, Daqing; Luo, Yi (Frontiers in Microbiology, 2020)
Antibiotics are frequently used to treat bacterial infections; however, they affect not only the target pathogen but also commensal gut bacteria. They may cause the dysbiosis of human intestinal microbiota and consequent metabolic alterations, as well as the spreading of antibiotic resistant bacteria and antibiotic resistance genes (ARGs). In vitro experiments by simulator of the human intestinal microbial ecosystem (SHIME) can clarify the direct effects of antibiotics on different regions of the human intestinal microbiota, allowing complex human microbiota to be stably maintained in the absence of host cells. However, there are very few articles added the antibiotics into this in vitro model to observe the effects of antibiotics on the human intestinal microbiota. To date, no studies have focused on the correlations between the bloomed pathogens caused by amoxicillin (AMX) exposure and increased functional pathway genes as well as ARGs. This study investigated the influence of 600 mg day–1 AMX on human intestinal microbiota using SHIME. The impact of AMX on the composition and function of the human intestinal microbiota was revealed by 16S rRNA gene sequencing and high-throughput quantitative PCR. The results suggested that: (i) AMX treatment has tremendous influence on the overall taxonomic composition of the gut microbiota by increasing the relative abundance of Klebsiella [linear discriminant analysis (LDA) score = 5.26] and Bacteroides uniformis (LDA score = 4.75), as well as taxonomic diversity (Simpson, P = 0.067, T-test; Shannon, P = 0.061, T-test), and decreasing the members of Parabacteroides (LDA score = 4.18), Bifidobacterium (LDA score = 4.06), and Phascolarctobacterium (LDA score = 3.95); (ii) AMX exposure significantly enhanced the functional pathway genes and beta-lactam resistance genes, and the bloomed pathogens were strongly correlated with the metabolic and immune system diseases gene numbers (R = 0.98, P < 0.001) or bl2_len and bl2be_shv2 abundance (R = 0.94, P < 0.001); (iii) the changes caused by AMX were “SHIME-compartment” different with more significant alteration in ascending colon, and the effects were permanent, which could not be restored after 2-week AMX discontinuance. Overall results demonstrated negative side-effects of AMX, which should be considered for AMX prescription.